THU0415 Etanercept as Monotherapy or in Combination with Conventional Disease-Modifying Anti-Rhuematic Drugs in Psoriatic Arthritis: Results from a Large, Prospective, Multicenter, Observational Study. (9th June 2015) - Lorenz, H.-M.; Behrens, F.; Lippe, R.; Jobst, J.; Löschmann, P.-A.; Meier, L.
Abstract : Background: Biologic tumour necrosis factor inhibitors (TNFi) are often used in combination with a conventional DMARD (cDMARD), mostly methotrexate, for the treatment of psoriatic arthritis (PsA). To date, there are no randomised controlled trials showing the superiority of TNFi in combination with cDMARDs versus TNFi monotherapy in PsA. Objectives: To investigate the efficacy of open-label etanercept (ETN) in patients treated by rheumatologists with ETN monotherapy or ETN+cDMARD combination therapy. Methods: A prospective, non-controlled, non-interventional, multicenter, observational study of patients with active PsA was conducted to assess the safety and efficacy of ETN in clinical practice. Patients aged ≥18 years in whom treatment with branded ETN had been initiated were enrolled. Standard clinical outcomes were assessed at baseline and at 6 visits over 52 weeks. In this subgroup analysis, the impact of concomitant use of cDMARDs on the efficacy of ETN in all patients and in those with exclusively peripheral arthritis was assessed. The treatment target of modified minimal disease activity (mMDA) was achieved when patients met 5/6 of the following criteria: tender/swollen joint counts (T/SJC (0 or 1), body surface area (BSA) ≤3%, patient pain visual analogue scale (VAS) ≤15, patient disease activity VAS ≤20, and SF-12 physical function >45. Results: A total of 1431 subjects were investigated; 576 in the subanalysis of exclusively peripheral arthritis. Baseline demographics were similar between the ETN and ETN+cDMARD groups. Baseline disease activity related to the joints was similar in both treatment groups but patients in the ETN group had higher BSA involvement than those receiving ETN+cDMARD (16.5% vs. 7.0%). Over 52 weeks, improvement of the affected BSA and disease activity in 28-joints (DAS28) was similar in the two treatment groups. No difference in BSA or DAS28 was seen between all patients and patients with peripheral arthritis only (Table 1 ). In the ETN vs. ETN+cDMARD group, 37.5% vs. 32.6%, respectively, of patients with peripheral-arthritis-only achieved mMDA. Conclusions: In this large prospective observational study of patients with active PsA treated with etanercept, no additional effect of concomitant cDMARD was seen on clinical efficacy. This was also confirmed in a peripheral-arthritis-only subgroup. High numbers of patients reached mMDA, independent of the additional use of cDMARDs. Acknowledgements: We wish to thank all patients who participated this study and medical staff of all participating centres. Medical writing support was provided by Samantha Forster of Engage and was funded by Pfizer Inc. Disclosure of Interest: H.-M. Lorenz Grant/research support from: Pfizer Inc., Speakers bureau: Honoraria from Abbvie, Roche, Chugai, MSD, Medac, UCB, Bristol Myers Squibb, and Janssen-Cilag, F. Behrens Grant/research support from: Pfizer Inc., Roche, Abbvie, and Chugai, Consultant for: Abbvie, Pfizer Inc., Celgene, Novartis, Chugai, Astra Zeneca, Lilly, Janssen, Merck, and Morphosys, Speakers bureau: Abbvie, Pfizer Inc., Celgene, Novartis, Chugai, UCB, Astra-Zeneca, Janssen, Roche, and Lilly, R. Lippe Shareholder of: Pfizer Inc., Employee of: Pfizer Inc., J. Jobst Shareholder of: Pfizer Inc., Employee of: Pfizer Inc., P.-A. Löschmann Shareholder of: Pfizer Inc., Employee of: Pfizer Inc., L. Meier: None declared